2020
DOI: 10.1021/acs.bioconjchem.0c00202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of New Trivalent Ligands for Hepatocyte Targeting via the Asialoglycoprotein Receptor

Abstract: Since the asialoglycoprotein receptor (also known as the "Ashwell−Morell receptor" or ASGPR) was discovered as the first cellular mammalian lectin, numerous drug delivery systems have been developed and several gene delivery systems associated with multivalent ligands for liver disease targeting are undergoing clinical trials. The success of these systems has facilitated the further study of new ligands with comparable or higher affinity and less synthetic complexity. Herein, we designed two novel trivalent li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
(91 reference statements)
2
4
0
1
Order By: Relevance
“…Therefore, the contribution of this ASGPR-specific mechanism is highly significant in the case of hepatocytes and allows faster internalization of conjugate 9 in line with the literature data reporting that effective cellular uptake of ASGPR-targeted compounds occurs even within the first 10 min of treatment followed by further slow accumulation up to 30–40 min . The specificity of GalNAc-mediated cellular uptake was proved in parallel experiments in the presence of high concentrations of competing monovalent (GalNAc) or trivalent (GalNAc) 3 ligands (10 mM, 10 6 to 10 4 molar excess), which efficiently inhibit internalization of compound 9 (Figure ) but not compound 8 in HepG2 (compare Figure S7a,b, middle and bottom panels, Supporting Information). Such high inhibiting concentrations of GalNAc were reported previously .…”
Section: Microscopy Experimentssupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the contribution of this ASGPR-specific mechanism is highly significant in the case of hepatocytes and allows faster internalization of conjugate 9 in line with the literature data reporting that effective cellular uptake of ASGPR-targeted compounds occurs even within the first 10 min of treatment followed by further slow accumulation up to 30–40 min . The specificity of GalNAc-mediated cellular uptake was proved in parallel experiments in the presence of high concentrations of competing monovalent (GalNAc) or trivalent (GalNAc) 3 ligands (10 mM, 10 6 to 10 4 molar excess), which efficiently inhibit internalization of compound 9 (Figure ) but not compound 8 in HepG2 (compare Figure S7a,b, middle and bottom panels, Supporting Information). Such high inhibiting concentrations of GalNAc were reported previously .…”
Section: Microscopy Experimentssupporting
confidence: 87%
“…Representative fluorescence (top) and bright-field (bottom) microscopy images of HepG2 cells treated with 1 μM of compound 9 either alone or in the presence of 10 mM of ASGPR-blocking ligands: monovalent GalNAc or trivalent (GalNAc) 3 . (For details see Supporting Information.…”
Section: Microscopy Experimentsmentioning
confidence: 99%
“…In other words, the hepatocyte-targeting capacity followed the W-1-5 (monoga-lactose) < W-2-9 (digalactose) < W-3-8 (trigalactose) order, obeying the rules of the galactose-recognition cluster effect toward ASGPR. Interestingly, it was reported that the galactose-modified bis-fluorophore conjugate, 24 the galactosamine-modified betulin conjugate, 25 and the trivalent galactosamine-modified Cy5 dye 26 showed a similar hepatocytetargeted tendency, also confirming the reliability of our results.…”
Section: ■ Introductionsupporting
confidence: 90%
“…Initially, two azide derivatives of N-acetyl-D-galactosamine 1 and 2 and also N-acetyl-D-glucosamine (GlcNAc) azide 3 were synthesized (Figure 1). We used β-azido glycosylation (FeCl 3 / TMSN 3 ) 32 or β-O-glycosylation (TMSOTf/2-azidoethanol) 33 reactions of β-D-galactosamine pentaacetate according to the previously published procedures, followed by alcoholysis of the O-acetyl groups by MeONa/MeOH. Esters 4−6 containing a residual 5-hexynoic acid moiety as a linker (Scheme 1) were synthesized in the second step.…”
Section: ■ Results and Discussionmentioning
confidence: 99%